Cognitive Behavioral Counseling using Cognitive Restructuring Techniques to Reduce Social Loafing in Middle School Students - Esther Lydia Rismawati; Ni Ketut Suarni; Wayan Eka Paramartha (Department of Guidance and Counseling, FIP, Undiksha, 2025)
Social loafing refers to the tendency of group members to exhibit reduced motivation or effort, to behave passively or remain silent in group settings, and to allow others to take responsibility for working on and completing group tasks. This study aimed to examine and describe the effectiveness of cognitive behavioral counseling using cognitive restructuring techniques in reducing social loafing among seventh-grade junior high school students. The research employed a quasi-experimental approach with a nonequivalent pretest–posttest control group design, in which an experimental class and a control class were selected based on the average scores obtained from a questionnaire. The population of this study consisted of seventh-grade junior high school students. Data analysis was conducted using parametric statistical analysis, specifically the independent samples t-test, followed by an effect size test. The results of the study indicate that cognitive behavioral counseling with cognitive restructuring techniques was effective in reducing social loafing among seventh-grade students at SMP Negeri 6 Singaraja. The results of the parametric statistical test using the independent samples t-test showed p < α (0.000 < 0.05). Therefore, it can be concluded that the alternative hypothesis (Ha) was accepted and the null hypothesis (H₀) was rejected, indicating that cognitive behavioral counseling is effective in reducing students’ social loafing.